2023
DOI: 10.3390/w15213740
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Contamination in Groundwater of Community Tube Wells, Source Distribution, Associated Health Risk Exposure, and Suitability Analysis for Drinking from Arid Zone

Zahid Ullah,
Abdur Rashid,
Javed Nawab
et al.

Abstract: Fluoride (F−) pollution in potable groundwater (GW) is a serious environmental concern in Pakistan with substantial human health hazard reports. The research on F− pollution in GW resources in Sindh Province is still incomplete. To explore the realistic conditions, the present research aimed to investigate the GW quality of community tube wells concerning F− contamination in Tharparkar, Sindh, Pakistan. A total of 53 samples were collected and examined for F−, along with other physicochemical parameters. The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Rock-water interaction controls the hydrochemistry of groundwater, and the aquifers likely contribute fluoride during weathering. A previous analysis demonstrated that geological and anthropogenic activity contaminated the studied area's groundwater resources [50].…”
Section: Present Studymentioning
confidence: 94%
“…Rock-water interaction controls the hydrochemistry of groundwater, and the aquifers likely contribute fluoride during weathering. A previous analysis demonstrated that geological and anthropogenic activity contaminated the studied area's groundwater resources [50].…”
Section: Present Studymentioning
confidence: 94%